2019
DOI: 10.1007/s00253-019-09631-3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial ecology of the cryosphere (glacial and permafrost habitats): current knowledge

Abstract: Microorganisms in cold ecosystems play a key ecological role in their natural habitats. Since these ecosystems are especially sensitive to climate changes, as indicated by the worldwide retreat of glaciers and ice sheets as well as permafrost thawing, an understanding of the role and potential of microbial life in these habitats has become crucial. Emerging technologies have added significantly to our knowledge of abundance, functional activity, and lifestyles of microbial communities in cold environments. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 116 publications
(119 reference statements)
4
72
0
Order By: Relevance
“…Study of microbial diversity in polar and high alpine regions has revealed a higher diversity of viruses, bacteria, and eukaryotic microbes than expected, and these extreme cold habitants are hot spots of microbial diversity and evolution ( Anesio and Bellas, 2011 ; Margesin and Collins, 2019 ). In the present study, we compared 21 genomes of psychrophilic Cryobacterium to their mesophilic counterparts from the same family Microbacteriaceae with the aim to identify unique genomic features of the psychrophilic Cryobacterium strains isolated from polar and alpine environments.…”
Section: Discussionmentioning
confidence: 99%
“…Study of microbial diversity in polar and high alpine regions has revealed a higher diversity of viruses, bacteria, and eukaryotic microbes than expected, and these extreme cold habitants are hot spots of microbial diversity and evolution ( Anesio and Bellas, 2011 ; Margesin and Collins, 2019 ). In the present study, we compared 21 genomes of psychrophilic Cryobacterium to their mesophilic counterparts from the same family Microbacteriaceae with the aim to identify unique genomic features of the psychrophilic Cryobacterium strains isolated from polar and alpine environments.…”
Section: Discussionmentioning
confidence: 99%
“…Such cold-loving microorganisms are known to have several modifications at cellular and biochemical levels to alleviate the effect of low temperatures and other associated stress conditions. These extreme low temperatures are dependent on these environment-specific microorganisms for their several ecological processes [8]. In the socio-economic perspective, Himalayan ranges serve as home to the population living in it.…”
Section: Himalaya: Geographic Importance and Its Uniquenessmentioning
confidence: 99%
“…These microhabitats exist in a wide variety of icy environments: snow, glacial ice, deep glacial ice, frozen ponds, sea ice, etc. (Margesin and Miteva, 2011 ; Margesin and Collins, 2019 ). For example, glacial ice cores collected from the West Antarctic Ice Sheet (WAIS) Divide borehole in Antarctica contained prokaryotic cell concentrations from 10 4 to 10 6 cells/cm 3 at a depth of 1.7–2.7 km below the surface (Santibáñez et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Priscu et al , 1998 , 1999; Price, 2006 ; Priscu and Hand, 2012 ; Boetius et al , 2015 ; D'Andrilli et al , 2017 ; Garcia-Lopez and Cid, 2017 ). In particular, understanding how organic materials (nutrients, building blocks) and microbial cells in terrestrial ice sheets are distributed and interrelated in ice microenvironments (Priscu et al , 2007 ; Margesin and Collins, 2019 ) will aid in the exploration of these alien worlds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation